The dilemma of English as a medium of instruction policy in science college programs - Munassir Alhamami; Abdullah Almelhi (Universitas Syiah Kuala, 2021)
Achieving science undergraduate programs learning outcomes relies on the students' proficiency in the language of instruction, a challenge that many policymakers ignore. This study is to understand the influence of English as a medium of instruction (EMI) policy in four undergraduate science programs, namely, Biology, Chemistry, Physics, and Mathematics, in Saudi Arabia. The data were collected from the following groups of participants: 1461 science alumni records, 769 current undergraduate science students' surveys, and 111 science university instructors' surveys. The results of alumni records indicated that grades of the intensive English program in the first year predict the alumni cumulative grade point average (GPA) once they finish their four-year program. The results demonstrated that the higher is the alumni's English proficiency, the better is their cumulative GPA. The results of the current science students' questionnaire showed their preferred language of instruction could be predicted by their attitudes and society's attitudes. Most of these students preferred to learn sciences in their native language (Arabic), which contradicted the policy of the current program. The instructors' questionnaire results showed that instructors held divergent perspectives on the usage of EMI and students' native language in the undergraduate science programs. To conclude, educationists and programs policymakers need to locate more attention and interventions toward the language of instruction. It is also recommended that universities provide science students with more English courses. Science students should also have English for science purposes courses to familiarize them with the science terms and prepare them to read science materials.